Alternaria-Brassica pathosystem: development and perspective (Journal of Oilseed Brassica, 2026)
A sudden outbreak of a plant disease might result in significant economic losses. Understanding the disease triangle, disease epidemics, and forecasting are all crucial in dealing with pathogens. The Genus Alternaria is a notorious fungus having 275 species, responsible for enormous economic losses varying from 10% to 70% in crucifers which are considered as major edible oil crops all over the world. The Alternaria blight/ black spot disease is the major bottleneck in the global production of commercial oilseed Brassicas. Among Alternaria species, A. brassicae, A. brassicicola, A. raphani, and A. alternata are well-documented for infecting several members of the Brassicaceae family. Recent advanced taxonomic investigations have yielded a wealth of data that may be used to outline the evolutionary lineages within Alternaria and related genera. In addition, some R genes/QTLs such as chitinase, endochitinase ‘ech42’, glucanase, PmAMP1, AbVF19, Amr1 etc. from host crop and non-hosts have also been identified through molecular markers targeting A. brassicae and A. brassicicola. Though the prediction models are available, but their practical utility is still limited for effective forewarning. Another problem is the lack of robust data on the potentiality of indigenous as well as exotic genetic resources with a resistance to Alternaria blight making the exploitation of non-host resistance (NHR) mechanisms unfeasible in protecting Brassica crops. The availability of resistant sources is not yet reported in the U triangle species. Thus, the focus of this review is to identify gaps and bottlenecks in our understanding of the Alternaria- Brassica pathosystem in multiple dimensions which could aptly incorporate in holistic management approach with a sustainable and profitable solution to deal with the black spot disease of crucifers.